The induction of YAP expression following arterial injury is crucial for smooth muscle phenotypic modulation and neointima formation - Wang, Xiaobo (2012)
OBJECTIVE: Abnormal proliferation and migration of vascular smooth muscle cells (SMCs) are the key events in the progression of neointima formation in response to vascular injury. The goal of this study is to investigate the functional role of a potent oncogene YAP in smooth muscle phenotypic modulation in vitro and in vivo. METHODS AND RESULTS: In vitro in cell culture and in vivo in both mouse and rat arterial injury models YAP expression is significantly induced and correlated with the vascular SMC synthetic phenotype. Over-expression of YAP promotes SMC migration and proliferation while attenuating smooth muscle contractile gene expression. Conversely, knocking-down endogenous YAP in SMCs up-regulates smooth muscle gene expression but attenuates SMC proliferation and migration. Consistent with this, knocking-down YAP expression in a rat carotid balloon injury model and genetic deletion of YAP specifically in vascular SMCs in mouse after carotid artery ligation injury attenuates injury-induced smooth muscle phenotypic switch and neointima formation. CONCLUSIONS: YAP plays a novel integrative role in smooth muscle phenotypic modulation by inhibiting smooth muscle-specific gene expression while promoting smooth muscle proliferation and migration in vitro and in vivo. Blocking the induction of YAP would be a potential therapeutic approach for ameliorating vascular occlusive diseases.